Pengaruh Media Visual Infografis terhadap Keterampilan Menulis Teks Eksposisi Siswa SMP Muhammadiyah Rappang - Anita Candra Dewi (FKIP UNSULTRA, 2025)
This study aims to investigate the effect of using visual infographic media on students’ expository writing skills in Grade VIII at SMP Muhammadiyah Rappang. The background of this research is the low ability of students to compose coherent, logical, and structurally appropriate expository texts. Infographics are considered capable of assisting students in understanding the flow of expository thinking through attractive and structured visual presentations. The method employed was a quasi-experimental design with a pretest-posttest control group approach. The research sample consisted of two classes: the experimental class, which utilized infographic media, and the control class, which received conventional instruction. The research instrument was an expository writing test, which had been tested for validity and reliability. Data were analyzed using normality tests, homogeneity tests, and hypothesis testing (t-test). The results indicated a statistically significant difference between the posttest scores of the experimental and control groups. The mean posttest score of the experimental group was notably higher than that of the control group, suggesting that the use of infographic media had a positive impact on improving students’ expository writing skills. Based on these findings, it can be concluded that visual infographic media is an effective alternative in writing instruction, particularly in teaching expository texts. This study recommends that Indonesian language teachers incorporate infographics as an instructional tool to support the development of students’ literacy skills, especially in the context of 21st-century education demands.